A Very Short, Fairly Interesting and Reasonably Cheap Book about Studying Organizations - Grey, Christopher, 1964- (UK: SAGE, 2022)
Written in an accessible style, this work presents a discussion of classical and contemporary ideas about organisations and their management. It shows that getting to grips with these ideas means asking fundamental questions about what it means to be human and about the nature of modern society.
Includes bibliographical references (pages 151-161) and index.
Keywords: Organizational behavior; Management; Comportement organisationnel; Gestion; management; Management; Organizational behavior